DEVELOPMENT OF SCIENCE LEARNING SET USING THE PROBLEM BASED LEARNING (PBL) MODEL IN ENVIRONMENTAL POLLUTION MATERIALS IN GRADE VII SMP NEGERI 5 JOMBANG IN 2018 - Raudatul Mahmuda; Nur Kuswanti; Noer Af”idah (Jurnal Pembelajaran Sains, 2021)
This research aims to overcome the problems which faced by the teachers and students is how teacher develop quality of learning tools that guide students in solving problems for learning science. The quality of learning with Problem Based Learning model is determined based on validation, practicality, and effectiveness. Validity is obtained based on the result of validity by the experts, practically is obtained based on the implementation of student learning and effectiveness is obtained based on the students’ posttest score. The development model used is the ADDIE model (Analyze, Design, Development, Implement, Evaluation). The results of this research showed that the learning tools by PBL model obtained of validation with the acquisition of an average score of 3.7 with very valid category, the implementation of learning reached 8.4 % with very practical category, students responses reached 97.6% with positive responses and students learning outcomes were known from mastery learning based on KKM reached 84.3 with very effective category. Based on these results it could be concluded that the Development of learning tools with Problem Based Learning model for class VIII on Environmental Pollution was stated qualified to be used.